Civic Education and Nationalism Attitudes of Elementary School Students: Implications for Child Well-Being and SDGs in Indonesia - Mikyal Hardiyati; Noni Putri; Asroruddin Lubis (Journal of Contemporary Gender and Child Studies, 2026)
Previous studies on civic education and nationalism have predominantly focused on secondary or tertiary levels, leaving a critical gap regarding how Pancasila and Civic Education (PPKn) shapes nationalism attitudes among elementary school students and its connections to child well-being aligned with Sustainable Development Goals (SDGs). This study investigates the role of PPKn instruction in cultivating nationalism attitudes among elementary school students in Kendari, Southeast Sulawesi, Indonesia, and explores implications for child well-being and SDG 4 (Quality Education) and SDG 16 (Peace, Justice, and Strong Institutions). A quantitative survey design was employed, involving 312 Grade V and VI students, 24 PPKn teachers, and 9 school principals across three public and private elementary schools selected through stratified random sampling. Data were collected using validated Nationalism Attitude Scales (Cronbach's α = .87) and PPKn Learning Quality Inventory (α = .83), then analysed via multiple regression and structural equation modelling (SEM). Results reveal that PPKn instructional quality significantly predicts nationalism attitudes (β = .61, p < .001), with participatory methods and contextual content as strongest mediators. Extracurricular integration amplified this effect. However, digital literacy gaps and inconsistent pedagogical competencies among teachers moderated outcomes. These findings suggest that strengthening PPKn through innovative, inclusive pedagogy contributes not only to nationalism formation but also to broader child well-being and democratic citizenship, advancing Indonesia’s SDG commitments.